Carnitine Is Associated With Atherosclerotic Risk and Myocardial Infarction in HIV‐Infected Adults. Issue 9 (7th May 2019) - Sinha, Arjun; Ma, Yifei; Scherzer, Rebecca; Rahalkar, Smruti; Neilan, Brendan D.; Crane, Heidi; Drozd, Daniel; Martin, Jeffrey; Deeks, Steven G.; Hunt, Peter; Hsue, Priscilla Y.
Abstract : Background: People living with HIV (PLWH) have an increased risk of myocardial infarction (MI). Changes in the gut microbiota that occur with chronic HIV infection could play a role in HIV‐associated atherosclerosis. Choline, carnitine, betaine, and trimethylamine N‐oxide are small molecules that are, in part, metabolized or produced by the gut microbiome. We hypothesized that these metabolites would be associated with carotid artery intima‐media thickness and MI in PLWH. Methods and Results: Carotid artery intima‐media thickness was measured at baseline and at a median interval of 4 years in 162 PLWH from the SCOPE (Study of the Consequences of the Protease Inhibitor Era) cohort in San Francisco, CA. Separately, 105 PLWH (36 cases with type I adjudicated MI and 69 controls without MI) were selected from the Center for AIDS Research Network of Integrated Clinical Systems, a multicenter clinic‐based cohort. Controls were matched by demographics, CD4 cell count, and duration of viral suppression. In the SCOPE cohort, higher carnitine levels had a significant association with presence of carotid plaque and greater baseline and progression of mean carotid artery intima‐media thickness after adjusting for traditional cardiovascular disease risk factors. In the treated and suppressed subgroup, these associations with carnitine remained significant after adjustment for cardiovascular disease risk factors. In the Center for AIDS Research Network of Integrated Clinical Systems cohort, the risk of MI was significantly increased in subjects with carnitine levels in the highest quartile after adjustment for cardiovascular disease risk factors. Conclusions: In PLWH, including the treated and suppressed subgroup, carnitine is independently associated with carotid artery intima‐media thickness, carotid plaque, and MI in 2 separate cohorts. These results emphasize the potential role of gut microbiota in HIV‐associated atherosclerosis and MI, especially in relation to carnitine metabolism.